A New MCR Strategy Generating a Collection of Skeletally Diverse Simple Molecules Combinatorially - Nandi, Sibaji; Gupta, Ajay; Kumar Pal, Amarta (Letters in Organic Chemistry, 2017)
Background: 1,4 Dihydropyridines (1,4 DHPs), chromeno[4,3-b] quinolines and pyrimido [4,5-b]quinolines are biologically and pharmaceutically important heterocycles. They are also present in many natural products. Many methods have been applied for their synthesis but each method has its own advantages as well as disadvantages. So, there is a scope to develop a new green and sustainable protocol for their synthesis. Methods: In this context, our aim was to develop an alternative platform for the synthesis of a collection of the small molecules with high scaffold diversity. Our methods based on Lewis acid catalyzed one-pot synthesis of 1,4-DHP, pyrimido[4,5-b]quinoline and chromeno[4,3-b]quinoline derivatives under room temperature stirring or refluxing condition. Results: We have standardized a protocol for the synthesis of a library of heterocycles such as 1,4- DHP, pyrimido[4,5-b]quinoline and chromeno[4,3-b]quinoline derivatives representing a collection of skeletally diverse simple molecules decorated with the combination of building blocks by an easy, inexpensive and simple reaction technique. With an optimized reaction condition we prepare the 1,4- DHPs and pyrimido[4,5-b]quinolines exclusively by iodine but interestingly we failed to prepare the chromeno[4,3-b]quinolones using iodine but it was successfully synthesized by Sc(OTf)3. 1,4-DHPs were synthesized by using 2 molecules of 4-aminocoumarin and 1 molecule of aromatic aldehydes and pyrimido[4,5-b]quinolines from one molecule each of 6-amino-1,3-dimethyl uracil, aromatic aldehydes, and dimedone by using iodine as a catalyst. Interestingly in the presence of iodine,4-aminocoumarin, aromatic aldehydes, and dimedone results in the formation of 1,4-DHP whereas catalytic amount of Sc(OTf)3 produces the chromeno[4,3-b]quinoline derivatives in a good to excellent yield. Conclusion: In conclusion, we have developed a mild, easy and simple way for the synthesis of 1,4- DHPs, chromeno[4,3-b]quinoline derivatives and pyrimido[4,5-b]quinolines combinatorially with a highly optimized reaction condition.The entire optimization protocol reflects the unique catalytic activity of non-metallic Lewis acid catalyst iodine with rare earth-transition metal catalyst Sc(OTf)3. We were able to generate skeletal diversity with the use of different building block via one synthesis-one skeleton approach. The advantages of our methodology lie in high yields, operational simplicity and chromatographic free separation with high skeleton diversity of the compound.
Keywords: Sc(OTf)3